Passionate and pious : religious media and black women's sexuality - Moultrie, Monique Nicole, 1978- (Duke University Press, 2017)
In Passionate and Pious Monique Moultrie explores the impact of faith-based sexual ministries on black women's sexual agency to trace how these women navigate sexuality, religious authority, and their spiritual walk with God. Providing churchwomen a space to candidly discuss these issues, these popular ministries exist largely beyond the traditional church, with dialogues about sex taking place in chat rooms and through text messages, social media, email, and other media. Moultrie foregrounds televangelist Juanita Bynum's construction of the black Christian sexual identity these ministries promote while emphasizing how churchwomen reconcile these prescriptive identities with their individual experiences. What does it mean for senior women to exercise sexual agency when their church standing could be questioned? What does celibacy mean for women who experience same-sex desire while believing that such desire goes against God's will? Advancing a womanist sexual ethics, Moultrie reframes biblical interpretations and conceptions of what constitutes a healthy relationship to provide a basis for sexual decision making that does not privilege monogamy or deny female pleasure, thereby calling on black churchwomen to experience responsible and life-enhancing sex.